Improving the resilience and productivity of smallholder farming systems through intercropping and data-driven fertilizer recommendations in Northern Ghana - Jizorkuwie, Abdul-latif Baamonyor; Masoud, Jalaludeen; Yeboah, Patricia Amankwaa; Ofosu-ampong, Kingsley; Abera, Wuletawu (2025)
In northern Ghana, smallholder farmers suffer low productivity because of low soil fertility, unpredictable rain and lack of adoption of improved practices. This study evaluated the combined benefit of site-specific fertilizer recommendations (SSF) and maize-cowpea intercropping in enhancing productivity and resilience. Demonstrations were conducted in ten communities in the Northern and Upper West regions. Two treatments were evaluated, maize-cowpea intercrop with SSF sand sole maize with farmer applied fertilizer rates. In each community, farmers were selected to replicate the maize-cowpea intercrop with SSFR on their own fields. The year 2024 had a long dry spell from mid-June to mid-August that affected many crops in many parts of the country including the study areas. However, the SSF + intercrop plots produced significantly higher maize grain yield (4,078 kg ha-1) than farmer practice (2,826 kg ha-1), showing some level of resilience against drought. Average yields from farmer replicated plots achieved 3,124 kg ha-1, higher than the regional average of 1,600 kg ha-1. The study shows that tailored fertilizer recommendations in combination with maize-cowpea intercropping can contribute to sustainable production and help bridge the yield gaps and improve food security in the Guinea savannah agroecological zone.